Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 351170 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Nymphalidae", { "or" : [ "Country is United States of America", "Country is Canada", "Country is Mexico" ] } ] } The dataset includes 351170 records from 113 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003989-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences